Implementation Plan in Response to Board-Endorsed Recommendations for the IEO Evaluation of IMF Performance in the Run-Up to the Financial and Economic Crisis. (Policy Papers; Policy Paper, 2012)
This paper presents a forward-looking management implementation plan (MIP) for the IEO evaluation. In addition to addressing the specific Board-endorsed IEO recommendations, the paper also tries to transcend a narrow interpretation by providing new implementation ideas where the Board saw merit in the IEO's general, if not specific, approach. For example, while the Board did not agree with the specific recommendation to create a risk-assessment unit, this paper takes a broader view and presents proposals to address the general concern of a lack of risk-focus in IMF surveillance.